The Diversity of Holothurioidea in the Intertidal Zone of the Pancur Shore of the Alas Purwo National Park - Riya Wulan Afrely; Moh. Imron Rosyidi; Susantin Fajariyah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
Holothurioidea well known as Sea Cucumber is one of the classes from the Echinodermata phylum. Sea cucumbers are benthic animals that move slowly. Currently they already identified about 1135 species. Their existence usually associated with abiotic factors such as water salinity, temperature, pH, wave motion, light intensity and the substrate. The ability of the Holothurioidea to adapt to the abiotic factors will affect species diversity. The research aims is to determine the species diversity in the intertidal zone at Pancur Shore of the Alas Purwo National Park. It includes the species composition, species diversity index and the index of equality The study was conducted on 14th-21st of June 2014, by using systematic plotting transect method. The results found: one order, one family, two generas and eight species. The Species diversity index of Holothurioidea at Pancur Shore is low (0.930) and the equality index classified uneven (0.447).Keywords: Holothurioidea, intertidal, diversity, evennes